2012
DOI: 10.1007/s00125-012-2625-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of experimental diabetic vascular leakage and pericyte apoptosis in mice by delivery of αA-crystallin with a recombinant adenovirus

Abstract: Aims/hypothesis The study aimed to evaluate the efficacy of recombinant adenovirus expressing αA-crystallin (Ad-αAc-Gfp) in reducing pericyte loss within retinal vasculature in early diabetes. Methods Diabetes was induced by streptozotocin injection into C57BL/6 mice. Ad-αAc-Gfp was delivered by intravitreous injection to the right eyes of mice 2 weeks before induction of diabetes. Vascular leakage was determined by fluorescent angiography, Evans Blue leakage assay and leucocyte adhesion test. Production of αA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 45 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…If the peptides can cross the blood retinal barrier, they may be useful for inhibiting apoptosis in such diseases. In fact, ␣-crystallin delivery has been shown to reduce pericyte loss in an experimental diabetes model (40). In addition, it has been shown that ␣A-crystallin is protective against experimentally induced autoimmune uveitis (41) and ischemic optic neuropathy (42).…”
Section: Discussionmentioning
confidence: 99%
“…If the peptides can cross the blood retinal barrier, they may be useful for inhibiting apoptosis in such diseases. In fact, ␣-crystallin delivery has been shown to reduce pericyte loss in an experimental diabetes model (40). In addition, it has been shown that ␣A-crystallin is protective against experimentally induced autoimmune uveitis (41) and ischemic optic neuropathy (42).…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that in EAE, the anti-inflammatory property of αB crystallin was not found to be due to influencing the adaptive immune response directly, but by binding and the subsequent modulation of the pro-inflammatory mediators in plasma [93]. In addition, intravitreal delivery of recombinant adenovirus expressing αA crystallin has been shown to protect against vascular leakage and effectively prevents pericyte loss and BRB breakdown in an experimental diabetes model [94]. Exogenous administration of αA crystallin attenuated corneal neovascularization in mouse models potentially by increasing the expression of soluble VEGFR1 [57].…”
Section: α-Crystallin and Its Constitutive Peptides As Therapeutic Momentioning
confidence: 99%
“…Investigations into the extralenticular roles of αB-crystallin have identified changes in expression levels linked to multiple neurological disorders (Renkawek et al, 1999; Clark and Muchowski, 2000; Ousman et al, 2007) and cancer (Stegh et al, 2008), and a mutation in αB-crystallin that causes an inherited cardiac myopathy (Vicart et al, 1998). Recent studies have detailed a range of extralenticular roles for αA-crystallin as well, including the protection of retinal cells against diabetes (Kim et al, 2012) and autoimmune uveitis (Rao et al, 2008; 2012), and a potential role in retinoblastoma tumor growth (Kase et al, 2009). Alpha A-crystallin has also been shown to be an inhibitor of pancreatic carcinogenesis (Deng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%